Deconstruction Cognitive Strategies: Are Students Truly Engaging in Connective Thinking or Merely Memorizing Patterns? - Tasni, Nurfaida; Syukriani, Andi; Upu, Hamzah (Jurnal Riset Pendidikan Matematika, 2025)
Connective thinking skills are an essential aspect of mathematics learning in higher education. However, students tend to rely on memorising patterns rather than developing conceptual thinking strategies, which results in failure when faced with non-routine problems. This study aims to analyse the characteristics of students' cognitive strategies and identify the factors influencing their choice of strategies. Using a qualitative approach with think-aloud techniques, in-depth interviews, and analysis of written work from undergraduate mathematics education students. The results show that students begin problem-solving through visualisation and pattern exploration, but only a few are able to perform logical generalisation. Reflection was found to be the primary trigger for the transformation of strategies from memorisation to connectivity, although there were still construction holes in the conceptual network. These findings contribute theoretically to the application of Toshio's schema and have practical implications for learning design that emphasises reflection and conceptual connectivity.